Analisis Pengaruh Brand Image dan Brand Origin terhadap Intensi Pembelian Produk Batik - Kussudyarsana, K; Irawati, Zulfa (Universitas Muhammadiyah Surakarta, 2018)
This study aims to analyze the brand image, brand origin and purchase intension. The model in this study refers to the theory of country of origin, which in essence a consumer will connect the perception of a product or brand based on the origin of manufacture. Sampling method used is Random sampling, with the number of respondents a number of 140 respondents. Methods of data collection, by survey and observation. The analytical tool used is multiple linear regression used to analyze the relationship between the origin of the brand, brand image, the impression of quality and purchase intention. This study confirms the influence of local origin and the impression of quality on purchasing intentions. This study also confirmed the influence of regional origin with the impression of quality. Survey results show that Solo Batik excels in brand reputation, favorite motifs and color preferences compared to other types of batik in Java.